JOB SATISFACTION FOR PHYSICAL EDUCATION TEACHERS AND ITS RELATIONSHIP TO JOB PERFORMANCE AND ORGANIZATIONAL COMMITMENT - Mouloud Kenioua; Bougherra Bachir; Foudil Samir Bacha (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
The purpose: this study was to investigate the relation and correlation between job satisfaction, job performance, and organizational commitment among physical education teachers. Material: The participants where 100 physical educations teachers' male and female from secondary schools. Job satisfaction, job performance, and organizational commitment were measured through a questionnaire has 05 axes. Results: The findings indicated that there was a strongly positive relationship between job satisfaction and job performance, and the same relationship between job satisfaction and organizational commitment. Conclusion: there is a need to create an appropriate environment to ensure the success of the professors of physical education as well as providing incentives and promotions through clear standards.